2018
DOI: 10.1097/md.0000000000011130
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glypican-3 is a predictor of poor prognosis in hepatocellular carcinoma

Abstract: Background:Glypican-3 (GPC3) has been widely recognized in the progression of liver tumors for several years. The relationship between overexpression of GPC3 and the poorer prognosis of patients with hepatocellular carcinoma (HCC) was performed by 2 meta-analyses. However, there were also some latest literatures that indicated different conclusions distinctly. It is necessary for us to carry out a meta-analysis by adding the latest data from current studies to explore the correlation between GPC3 and prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
4
46
2
Order By: Relevance
“…The results showed that overexpression of GPC3 may indicate a poor prognosis. The high expression of GPC3 was significantly associated with malignant events such as poor tumor differentiation, advanced stage of tumor, vascular invasion, and HBV infection [66].…”
Section: Prognostic Value Of Gpc3 Expression In Patients With Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that overexpression of GPC3 may indicate a poor prognosis. The high expression of GPC3 was significantly associated with malignant events such as poor tumor differentiation, advanced stage of tumor, vascular invasion, and HBV infection [66].…”
Section: Prognostic Value Of Gpc3 Expression In Patients With Hccmentioning
confidence: 99%
“…Lots of tissue microarray and immunohistochemical data showed that GPC3 is highly expressed in more than 70% of HCC samples, but not in normal liver tissues, benign liver lesions, liver cirrhosis or hepatitis tissues [5,[63][64][65]. Also, the expression level of GPC3 is correlated with prognosis [66][67][68][69]. In addition, GPC3 is also highly expressed in some other cancers such as hepatoblastoma [70], lung squamous cell carcinoma [71], ovarian yolk sac tumor [72], melanoma [73], and urothelial carcinoma [74].…”
Section: Gpc3 As a Target For Clinical Diagnosis And Its Significancementioning
confidence: 99%
“…Many studies have reported that GPC3 expression is correlated with a poor prognosis in HCC [ 38 , 39 ], and that GPC3 may be a prognostic marker for curative resection [ 40 , 41 , 42 ] and HCC recurrence following liver transplantation [ 43 ]. Two meta-analyses recently indicated that GPC3 overexpression was significantly associated with poor prognosis in patients with HCC [ 44 , 45 ].…”
Section: Cell Surface Proteoglycan (Glycosylphosphatidylinositol-amentioning
confidence: 99%
“…Taken together, these findings suggest that patients with higher plasma GPC3 levels are in more advanced stages of HCC. Indeed, it has been reported that the expression of tumoral GPC3 increases with tumor progression . These results seem to suggest that the cut‐off value of plasma GPC3 levels reflects tumoral GPC3 expression in patients with HCV‐related HCC.…”
Section: Resultsmentioning
confidence: 75%